Cage enrichment to minimize aggression in part-time group-housed female breeding rabbits - Van Damme, Liesbeth G. W.; Ipek, Nusret; Verwaeren, Jan; Delezie, Evelyne; Tuyttens, Frank A. M. (Frontiers in Veterinary Science, 2024)
In most rabbit farms, breeding does kindle and nurse their kits in single-litter cages throughout their entire reproduction cycle. Protective behavior, however, induces aggressive displays and injuries when does are housed in groups. This study aimed to evaluate cage enrichment for reducing agonistic behavior in part-time group-housed does. Eighty does with their 22 days old kits were allocated to 20 multi-litter cages so that each cage housed four does and their litters for a period of 10 days. Each multi-litter group was subjected to one of four treatments: alfalfa blocks as distraction material (A), wooden panels underneath the platforms (P), both alfalfa and wooden panels (AP), or no extra enrichment (controls, C). This experiment was replicated for three consecutive reproduction cycles. Doe and kit skin injuries were scored before grouping and one, three, six, eight and ten days after grouping with a tagged visual analogue scale. Computer vision techniques were used to monitor rabbit activity continuously and to monitor agonistic behavior (aggression and fleeing/chasing) continuously during the first 24 h after grouping during light hours. During the first day in group, 67.2% of the does and 13.4% of the kits acquired new injuries. This increased to respectively 82.0% and 33.2% after ten days in group relative to the onset of grouping. Doe injury scores increased towards the sixth day after grouping compared to the first (P<0.001), and were highest on the tenth day for the kits (P<0.001). On all observation days, the number of injured does was higher in C compared to the A (P=0.04) and AP treatment (P=0.005). No other treatment effects on doe or kit skin injuries were observed. Rabbit activity was highest after grouping but decreased after the first and second day (P<0.001). Agonistic interactions between does involved more fleeing/chasing behavior (62.0%) than aggression (38.0%). Although hierarchy fights are likely when group housing unacquainted does, the many animals that sustained injuries and the high injury scores confirm that part-time group housing for does is challenging and possibly inevitable. This study has shown that alfalfa, with or without wooden panels, can slightly reduce the number of injured does.